“Debriefing and Organizational Lessons Learned” (DOLL): A Qualitative Study to Develop a Classification Framework for Reporting Clinical Debriefing Results - Paquay, Méryl; Dubois, Nadège; Diep, Anh Nguyet; Graas, Gwennaëlle; Sassel, Tamara; Piazza, Justine; Servotte, Jean-Christophe; Ghuysen, Alexandre (Frontiers in Medicine, 2022)
Background: The COVID-19 crisis has radically affected our healthcare institutions. Debriefings in clinical settings provide a time for the clinicians to reflect on the successes (pluses) and difficulties (deltas) encountered. Debriefings tend to be well-received if included in the broader management of the unit. The goal of this study was to develop a framework to categorize these debriefings and to assess its worthiness. Methods: A qualitative approach based on a grounded theory research method was adopted resulting in the DOLL framework. Debriefings were conducted within two Emergency Departments of a Belgian University Hospital during an 8-week period. As first step, three researchers used debriefing transcripts to inductively develop a tentative framework. During the second step, these three researchers conducted independent categorizations of the debriefings using the developed framework. Step 3 was to analyze the data and understand the utility the framework. Chi-square was conducted to examine the associations. Results: The DOLL is composed of 7 dimensions and 13 subdimensions. Applied to 163 debriefings, the model identified 339 items, including 97 pluses and 242 deltas. Results revealed that there was an association between the frequency of pluses and deltas and the dimensions (p<0.001). The deltas were mainly related to the work environment (equipment and maintenance) (p<0.001) while the pluses identified tended to be related to the organization of the unit (communication and roles) (p<0.001). With leadership’s support and subsequent actions, clinicians were more enthusiastic about participating and the researchers anecdotally detected a switch towards a more positive organizational learning approach. Conclusion: The framework increases the potential value of clinical debriefings because it organizes results into actionable areas. Indeed, leadership found the DOLL to be a useful management tool. Further research is needed to investigate how DOLL may work in non-